The emperor's caretaker. 5 - Hiiragi, Ichiha; Shouoto, Aya, 1977- (Square-Enix Manga & Books, 2025)
Linhua and company head to Heiyang, the capital of Guangyan, on an official visit. Emperor Zhiyou is captivated by the vibrant city, but Linhua finds herself unprepared for the next stop on their tour: her family home. Linhua's mother meets Souren, her daughter's secret fiancé, for the very first time. What will this encounter mean for their clandestine engagement?